POTENSI ENERGI LAMUN UNTUK MENDUKUNG PELESTARIAN DUGONG (DUGONG DUGON) DI DESA BERAKIT DAN DESA PENGUDANG PULAU BINTAN - Nurul Dhewani Mirah Sjafrie (Widyariset, 2018)
Dugong dugon is belong of the Order Sirinedae, family Dugonidae, known as a seagrass specialist and been categorized into endangerd species. In Bintan Island, these animals are found in the North season (December to February). This study aims to determine the potential of seagrass energy as dugong food which appeared in the Berakit and Pengudang village. Collecting of seagrass biomass was conducted in May 2015. A total of 40 transects squares measuring 1 x 1 meter used to take seagrass biomass. Seagrass energy is obtained by converting biomass into energy units. The result shows that seagrass energy in the Berakit village are 1.04 x 1012 Joule or can feed 51,000 – 88,000 dugong, whereas the Pengudang village are 6.64 x 1011 Joule or can feed 32,000 – 55,000 dugong. The potential seagrass derived from Halodule uninervis in Pengudang village can feed 589 - 1000 dugong. The seagrass in both of villages have great potential for dugong feed but the anthropogenic disturbances should be considered.  It is suggested that seagrass on the eastern coast of Bintan Island need to be managed seriously.